The Need for Accessible Health Education - Laughlin, Michael K.; Benes, Sarah; Sherlock-Shangraw, Rebecca (Journal of Physical Education, Recreation and Dance, 2026)
Health education in preschool through 12th grade is an essential component of a well-rounded education and can positively impact student health and well-being. All school-age students deserve access to high-quality, effective health education. However, students with disabilities may not be receiving the health education they are entitled to for many reasons, including that there is not a clearly defined understanding of health education for students with disabilities. Working from the perspective that health education is both a social justice imperative and an important component of students’ “well-rounded education” under the Every Student Succeeds Act of 2015, this article is a call to action and brings attention to this area of need. It is framed around three critical questions: (1) Why do students with disabilities deserve access to health education? (2) How should health education for students with disabilities be conceptualized? (3) Where does accessible health education go from here? By articulating these questions and providing initial thoughts to spur further discussion and action, this article encourages invested partners and collaborators to address this critical need so that students with disabilities can meaningfully access the same high-quality health education opportunities as their peers. © 2026 SHAPE America.
Keywords: dept.hms